2003
DOI: 10.1097/01.ju.0000095460.12999.43
|View full text |Cite
|
Sign up to set email alerts
|

Serum Pro Prostate Specific Antigen Improves Cancer Detection Compared to Free and Complexed Prostate Specific Antigen in Men With Prostate Specific Antigen 2 to 4 Ng/Ml

Abstract: The %pPSA significantly improved specificity for cancer detection and decreased the number of unnecessary biopsies in the PSA 2 to 4 ng/ml range. This relative improvement of %pPSA compared to % free PSA and complexed PSA was maintained throughout the PSA range of 2 to 10 ng/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(86 citation statements)
references
References 18 publications
3
75
0
8
Order By: Relevance
“…Sokoll and Catalona found that the percentage of pro-PSA could significantly decrease the number of unnecessary biopsies in men with a PSA between 2 and 4 ng ml À1 . 47,48 Moreover, 2-pro-PSA, a truncated form of pro-PSA, had the highest specificity for PCa screening and was the most efficient predictor of PCa aggressiveness. 49 Intact free PSA is similar to native PSA, but enzymatically inactive.…”
Section: Free Psa Isoformsmentioning
confidence: 99%
“…Sokoll and Catalona found that the percentage of pro-PSA could significantly decrease the number of unnecessary biopsies in men with a PSA between 2 and 4 ng ml À1 . 47,48 Moreover, 2-pro-PSA, a truncated form of pro-PSA, had the highest specificity for PCa screening and was the most efficient predictor of PCa aggressiveness. 49 Intact free PSA is similar to native PSA, but enzymatically inactive.…”
Section: Free Psa Isoformsmentioning
confidence: 99%
“…48 -50 Other PSA isoforms have been reported to be related to the risk of prostate carcinoma detection. 51,52 These observations have modulated recommendations for prostate biopsy in some settings. Most often, these factors have affected recommendations for a repeat prostate biopsy after an initial negative biopsy.…”
Section: Psa Isoformsmentioning
confidence: 99%
“…[14] Naya et al [37] , indicated lack of any significant difference between patients with or without PCa as for pPSA values, and % pPSA within a tPSA interval 4.4-8.5 ng/mL. Catalona et al [38] observed increases in % pPSA values in PCa patients with tPSA values varying between 2, and 10 ng/mL, and stated that % pPSA has higher diagnostic sensitivity, and specificity for PCa when compared with % fPSA without any correlation between histopathological stage, and % pPSA. Mikolajczyk et al [39] also pointed out to higher specificity, and positive predictive value of % pPSA rather than % fPSA for PCa in cases with tPSA values between 4, and 10 ng/mL.…”
Section: Propsa (Ppsa)mentioning
confidence: 99%